Diagnosed behavioral health conditions during the perinatal period among a commercially insured population by race/ethnicity, 2008–2020 - Beck, Dana C.; Tabb, Karen; Tilea, Anca; Vance, Ashlee J.; Hall, Stephanie; Schroeder, Amy; Zivin, Kara (Frontiers in Public Health, 2024)
The authors of this manuscript selected Frontiers in Psychiatry's open research topic "Women in Psychiatry 2023: Mood Disorders" for this submission, as this study centralizes behavioral health diagnoses of women during their childbearing experiences. Prevalence and trends of diagnoses, and the racial and ethnic variations therein, further highlight knowledge that can inform health services policy, further research, and clinical practice. The study team is fully comprised of researchers who identify as female, further suiting this work to this journal's research topic and aim of providing a platform for women in psychiatry.